Integrasi syariat, akhlak, dan tasawuf sebagai fondasi epistemologis pendidikan antikorupsi dalam pemikiran islam - Ghoni, Muhammad Abdul (Maliki Interdisciplinary Journal, 2026)
Anti-corruption education from an Islamic perspective requires the integration of sharia, morals, and Sufism to shape individuals who not only understand the law but also possess moral and spiritual integrity. Sharia provides a clear legal framework, morals foster honest and responsible behavior, while Sufism strengthens self-control and spiritual awareness. This integration shapes individuals who recognize that positions and wealth are entrusted to them by God, making corruption an act that not only violates the law but also damages the relationship with God. This education is expected to produce a generation with integrity, honesty, and responsibility, as well as a strong spiritual awareness to reject corruption. Thus, Islamic-based anti-corruption education serves as a long-term prevention strategy for building a just and moral civilization.